A review of simulink for single-phase rectifier - Salam Waley Shneen; Roshen Tariq Ahmedhamdi; Moafaq K.S. Al-Ghezi (International Journal of Advances in Applied Sciences, 2022)
The current review aimed to i) Simulate the work of electronic transformer; ii) Analyze and design different types of electronic transformer; and iii) Identify the most important joints of the topic in the work of the electronic transformer by evaluating and improving the system components. The number of electronic keys has been approved in terms of representing the number of phases on one side and the type of wave on the other hand such as one-half phase full wave or wave, as well as single-phase, which will be detailed later. The type of electronic keys has also been adopted in terms of the representation of electronic keys in the form of a diode, a transistor, or a thyristor.